Hydrodynamic and sediment dynamic impact of human engineering activity on Liyashan oyster reefs, China - Luo, Feng; Chen, Zhipeng; Wu, Hongbo; Zhu, Fei; Zeng, Jingwei; Quan, Weimin (Frontiers in Marine Science, 2022)
As human activity increases, coastal ecosystems are becoming increasingly vulnerable to a range of challenges. Oyster reefs are coastal ecosystems that provide habitats for a diverse range of marine species while also purifying water and providing natural coastal defense. However, because of human activity, global oyster reef areas have drastically diminished and are in grave danger. Simultaneously, it is impossible to determine the negative impact of human engineering activity on oyster reefs, due to the lack of intuitive and quantitative study methodologies. To address this issue, we applied a hydrodynamic model to analyze the impact on oyster reefs. First, we considered that human engineering activity, that is, coastal engineering, mainly affects the development of Liyashan Oyster Reefs by influencing hydrodynamics, sediment concentration, and bed-level evolution. We then applied MIKE3 to establish and validate a 3D hydrodynamic model of the southern part of the Yellow Sea around oyster reefs. Results showed that regional variations in flow velocity and suspended sediment concentration occurred in oyster reef waters, but the magnitude of these variations was limited. However, seabed elevation increased substantially in the Center Protection Area, which had a negative impact on oyster reefs. In general, our study provided a paradigm for analyzing the degree of impact on oyster reefs, showed the advantages of hydrodynamic models in quantitatively analyzing impact factors, and had reliable results.